(untitled) (Research, Society and Development, 2020)
Objective: To assess the clinical evolution of patients with Multiple Drug-Resistant Tuberculosis treated in a referral center in the Amazon region, between the years 2010 to 2014. Methods: Cross-sectional, descriptive and quantitative approach research, through the collection of patient data attended at Hospital Universitário de Belém do Pará, between the years 2010 and 2014. Results: There was a predominance of males and a faixa age most affected was in the most productive phase (18 to 55 years old), secondary to teaching 94.1% were present in two cases, or time of diagnosis and initiation of treatment from 1 to 10 days appeared in the majority, how many years profile of drug resistance prevailing with rifampicin, isoniazid and streptomycin and most associated comorbidities foi or diabetes. Conclusion: There is a great complexity surrounding the aspects related to the treatment of Tuberculous Resistant to Multiple Medications, and that these factors contribute to the maintenance of two high teaching indices, as well as a scarcity of technologies such as rapid diagnosis of the teaching and availability of more alternatives of most effective treatment. The limiting factor of the investigation is due to the fact that it is a matter of medical records, there is no pattern of records in some, with little information.